2020
DOI: 10.1097/j.pain.0000000000002110
|View full text |Cite
|
Sign up to set email alerts
|

Optogenetic inhibition of the colon epithelium reduces hypersensitivity in a mouse model of inflammatory bowel disease

Abstract: Visceral pain is a prevalent symptom of inflammatory bowel disease (IBD) that can be difficult to treat. Pain and hypersensitivity are mediated by extrinsic primary afferent neurons (ExPANs) that innervate the colon. Recent studies indicate that the colon epithelium contributes to initiating ExPAN firing and nociceptive responses. Based on these findings we hypothesized that the epithelium contributes to inflammation-induced hypersensitivity. A key prediction of this hypothesis is that inhibition of the epithe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 32 publications
(40 reference statements)
3
10
0
Order By: Relevance
“… 5 In other studies, it was found that decreasing activity of epithelial cells reduced pain associated with colon inflammation. 6 These findings contribute to a growing body of research that is defining how epithelial cells communicate with nerve fibers, glial cells, and immune cells within the gut and the functional significance of these interactions. They also support the prioritization of treatment strategies for IBD that promote repair of the epithelial lining as a means to reduce pain.…”
Section: Introductionmentioning
confidence: 79%
See 4 more Smart Citations
“… 5 In other studies, it was found that decreasing activity of epithelial cells reduced pain associated with colon inflammation. 6 These findings contribute to a growing body of research that is defining how epithelial cells communicate with nerve fibers, glial cells, and immune cells within the gut and the functional significance of these interactions. They also support the prioritization of treatment strategies for IBD that promote repair of the epithelial lining as a means to reduce pain.…”
Section: Introductionmentioning
confidence: 79%
“…Stimulation of the colon epithelium engages neural circuits, suggesting that a reduction in epithelial activity might inhibit neuronal firing and in so doing, reduce visceral nociception (VMRs). Studies done using mice that express the inhibitory yellow light-activated Arch-EGFP protein in colon epithelial cells (Vil-Arch mice) showed this to be the case 6 ( Figure 2A ). The ability of Arch-mediated inhibition of epithelial cells to block pain was assessed by in vivo measure of VMRs in response to colorectal distension in the presence or absence of Arch stimulation.…”
Section: Inhibition Of Epithelial Cells and Nerve Activitymentioning
confidence: 91%
See 3 more Smart Citations